Social interaction amid COVID-19 and responses to the pandemic in Sarawak - Liau, Juna; Sharifah Sophia Wan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article documents social interaction among rural and urban indigenous communities in Sarawak during the COVID-19 pandemic and their responses to the outbreak at individual, household and community levels. The study on social interaction is crucial to shed light on larger social institutions and to examine how social actions are organized across space and time. The study framed within the symbolic interactionist perspective - emphasize the role of symbols and language as the core elements of social interaction. Research methods used in the study are participant observation and interviews to understand relevant context and process. In participant observation, researchers took part in socio-cultural activities of the community in the villages and their dwellings places in urban areas and participated in social media platforms. Data from observation and interactions (face-to-face or mediated by technology) analysed based on themes and contents. The findings show that social interaction among community members significantly altered during the pandemic in terms of the mode of interactions, frequencies, locations, reasons, duration, types and topics of interactions. These include the shift of face-to-face interactions to digital interactions, reduced numbers of interactions, significant more home-based interactions, and then unequal access to digital interactions. Other findings highlight that cultural themes related to communalism, supernaturalism and family and/or children influenced the community members’ engagement in social interactions. The community responses towards the outbreak varied according to the socio-economic background of individuals and households. Through these data the study shed light on how community members interacted during the pandemic; the exchanged of ideas and information, conflict during interactions, responses to the pandemic and the issues surround inequality of access to information and communication technologies.